Management of University Social Responsibility in business schools. An exploratory study. Issue 2 (July 2020) - Wigmore-Álvarez, Amber; Ruiz-Lozano, Mercedes; Fernández-Fernández, José Luis
Abstract: Social Responsibility (SR) has become a key issue in higher education. The objective of this investigation is to reflect on the adoption of SR in universities. This paper explores how business schools are integrating SR into their management systems and analyzes the potential influence of variables such as the school's size and/or geographical area. A questionnaire obtained information to be analyzed and was complemented with information from websites and telephone interviews. A descriptive analysis was used to carry out a transversal analysis, allowing this paper to investigate the level of University Social Responsibility (USR) development in Global Network for Advanced Management (GNAM) institutions. Parametric and non-parametric tests were applied in order to determine the level of influence that the size and geographic location of the institution had on the level of integration of SR with the management. A certain degree of commitment of these institutions to SR was observed, as well as their concern about giving visibility to their SR actions. The influence of those models on the presence of the organization in a specific geographical area was not observed, nor did the organization size variable have an influence, with the exception of the areas of Society and Supply Chain. Highlights: Social Responsibility has become a key issue in higher education, including for business schools. Business schools have an interest in giving visibility to their actions and communicating them to their stakeholders. Few business schools have integrated Social Responsibility into their management system. Social Responsibility initiatives, both sector-specific and non-sector specific, must be made known to business schools. The size and geographic area of the organizations do not influence the socially responsible behavior of business schools.